The Utilization of WhatsApp in Increasing Knowledge of Integrated Services Post (Posyandu) Cadres on Preventing COVID-19 - Yulia Suciati; Yenny Zulhamidah; Wening Sari (Nusantara Science and Technology Proceedings)
Integrated Services Post (Posyandu) Cadres are a volunteer that helps to manage community health care issues. Normally, they play an important role in mother, child, and elderly health issue prevention and promotion. However, in the COVID-19 pandemic time, the role of Posyandu cadres should be optimized for the prevention of the disease. This research aimed to assess the efficacy of the utilization of WhatsApp in increasing knowledge of Posyandu cadres on preventing COVID-19, through Whatsapp group (WAG). The Quasi-experiment was conducted on 30 cadres in Bekasi Barat. They were invited to received counseling sessions using the Whatsapp Group (WAG) on how to prevent the disease and how to correctly use the mask. They were provided with all the counseling material that they could read before the question and ask session with the mentor. Changes in the knowledge level of the cadres were assessed using the pretest and post-test methods. There was a significant increase in the level of knowledge (Wilcoxon Signed Ranks Test, p = 0.004) which was indicated by a higher post-test score (mean 75.46) than the pre-test score (mean 60.69). The correct use of masks was the cadres’ most significant increase in knowledge post-WAG-counseling session. Most of the cadres enjoyed the education process through WAG and would like to use the educational materials as a tool to provide education to the wider community. Education through WAG is effective for increasing the knowledge of Posyandu cadres about COVID-19 prevention and can be emulated by cadres to educate the wider community